Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
1976
DOI: 10.1017/s0047404500006849
|View full text |Cite
|
Sign up to set email alerts
|

Is Sybil there? the structure of some American English directives

Abstract: Directives to hearers can be expressed in a variety of syntactic forms. The social distribution of such forms shows them to occur systematically, according to familiarity, rank, territorial location, difficulty of task, whether or not a duty is normally expected, whether or not non-compliance is likely. Except for some hints and questions not mentioning what is desired, directives do not require inference from a prior literal interpretation to be understood. Indeed, misunderstandings and puns imply that the in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

7
285
1
11

Year Published

1980
1980
2006
2006

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 555 publications
(304 citation statements)
references
References 14 publications
7
285
1
11
Order By: Relevance
“…For applied linguists concerned with language acquisition and with intercultur al communicati on, the insights gained through analysis of the social aspects of language use are of particular importance. Recent studies of such speech acts as apologies (Cohen and Olshtain 1981, Olshtain 1983, Olshtain and Cohen 1983, directives (Ervin-Tripp 1976, Blum-Kulka 1982 In earlier work on the analysis of complimentin g behavior among middle-clas s Americans (Manes and, it was demonstrate d that there exists a considerabl e (and previously unsuspected) amount of patterning both at the syntactic and the semantic levels. Examination of a corpus of approximate ly seven hundred examples of compliments uttered"in day-to-day interaction s and collected ethnographically , revealed that the spontaneity with which they are often associated is linked more to their freedom of occurrence within an <inter-action than to any originality in structure or lexicon.…”
Section: University Of Pennsylvani Amentioning
confidence: 99%
See 1 more Smart Citation
“…For applied linguists concerned with language acquisition and with intercultur al communicati on, the insights gained through analysis of the social aspects of language use are of particular importance. Recent studies of such speech acts as apologies (Cohen and Olshtain 1981, Olshtain 1983, Olshtain and Cohen 1983, directives (Ervin-Tripp 1976, Blum-Kulka 1982 In earlier work on the analysis of complimentin g behavior among middle-clas s Americans (Manes and, it was demonstrate d that there exists a considerabl e (and previously unsuspected) amount of patterning both at the syntactic and the semantic levels. Examination of a corpus of approximate ly seven hundred examples of compliments uttered"in day-to-day interaction s and collected ethnographically , revealed that the spontaneity with which they are often associated is linked more to their freedom of occurrence within an <inter-action than to any originality in structure or lexicon.…”
Section: University Of Pennsylvani Amentioning
confidence: 99%
“…For applied linguists concerned with language acquisition and with intercultur al communicati on, the insights gained through analysis of the social aspects of language use are of particular importance. Recent studies of such speech acts as apologies (Cohen and Olshtain 1981, Olshtain 1983, Olshtain and Cohen 1983, directives (Ervin-Tripp 1976, Blum-Kulka 1982, expressions of disapproval (d'fl.mico-Re isner 1983), and compliments , Wolfson and Manes 198D, Manes 1983, Wolfson 1981) have rich implication s. It has been demonstrated again and again that beneath the surface structure of the linguistic forms and the social etiquette invalved in their use, lies a gold mine of information about the value systems of speakers. In studying apologies, for example, we learn what constitutes an offense, and in studying compliments we learn about what speakers value.…”
Section: University Of Pennsylvani Amentioning
confidence: 99%
“…The subjects were asked to rate each request on three 5-point Likert-type scales: powerfulweak, rude-polite, and humble-arrogant. Previous research (Becker, 1982(Becker, , 1986Ervin-Tripp, 1976) demonstrated that speakers tendto address moreexplicit requests to lower status listenersand more ambiguous requeststo higherstatuslisteners, and that listenerstend to judge explicitrequests as rudeandjudgemore ambiguous requests as polite. Beckeret al were interestedin the interactive effects of speaker status and request form on listeners' judgments of requests, particularly when the request forms were not those typically used by speakers of particular statuses.…”
mentioning
confidence: 98%
“…"), Each of these ways of indirectly requesting the salt exploits a different condition for the felicitous performance of a request; they differ in their syntactic form (i.e., dec1aratives vs. interrogatives) and propositional content (i.e., the hearer's salt-passing abilities vs. the speaker's wishes). Ervin-Tripp (1976) and Lakoff (1977) have suggested that cultural conventions determine the form of speech acts. The acceptability of "Pass the salt," "I would like some salt," and "Could you pass the salt?"…”
mentioning
confidence: 99%